Chinese philosophy - Wen, Haiming, 1973- (New York ; Cambridge)
[2], 164, [1] s.
Keywords: "In this illustrated introduction Wen Haiming explores the characteristics of different philosophers in Chinese history and distinguishes the 'Chinese philosophical sensibility' motivating their thoughts. Employing Western philosophical categories to describe significant issues in the history of philosophy, Wen Haiming considers Chinese political philosophy in the pre-Qin era, Chinese metaphysics from Han to Tang dynasties, Chinese epistemology from Song to Ming dynasties and modern Chinese-Western comparative philosophy. Chinese Philosophy provides a clear, accessible conception of the Chinese philosophical sensibility and its evolution throughout history." --